1987
DOI: 10.1159/000457737
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Fetal Hepatic Cytochrome P-450-Associated 7-Ethoxyresorufin O-Deethylase and Aryl Hydrocarbon Hydroxylase Activities by Monoclonal Antibodies

Abstract: Two cytochrome P-450-dependent enzyme activities, 7-ethoxyresorufin O-deethylase (ERDE) and aryl hydrocarbon hydroxylase (AHH) were measured in liver microsomes from 7 human fetuses. Monoclonal antibodies (MAb) to a 3-methylcholanthrene- induced (MAb 1-7-1) and a phenobarbital-induced (MAb 2-66-3) rat hepatic cytochrome P-450 were used to measure the contribution of the MAb-defined, epitope-specific cytochromes P-450 to the total reaction measured for the above activities. MAb 1-7-1 inhibited fetal hepatic ERD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
6
6
0
Order By: Relevance
“…Pelkonen et al 1986;Pasanen et al (1987) arrived at similar results with human adult liver although the MAb 1-7-1 inhibiting potency varied more (0 to 65 per cent) than in our material. These data suggest that there are at least two enzymes or classes of enzymes responsible for 7-ethoxyresorufin 0deethylation since only 21 to 36 per cent of the activity was blocked by MAb 1-7-1.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Pelkonen et al 1986;Pasanen et al (1987) arrived at similar results with human adult liver although the MAb 1-7-1 inhibiting potency varied more (0 to 65 per cent) than in our material. These data suggest that there are at least two enzymes or classes of enzymes responsible for 7-ethoxyresorufin 0deethylation since only 21 to 36 per cent of the activity was blocked by MAb 1-7-1.…”
Section: Discussionsupporting
confidence: 79%
“…The other P-450 is responsible for only a part of 7-ethoxyresorufin 0-deethylation. Pelkonen et al 1986;Pasanen et al (1987) arrived at similar results with human adult liver although the MAb 1-7-1 inhibiting potency varied more (0 to 65 per cent) than in our material. This may be due to a difference in the environmental exposure of the individuals from whom the tissue was collected.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Evidence for the presence of constitutively expressed CYP1A1 enzyme in the fetus is compelling. In 1987, Pasanen et al (1987) reported ethoxyresorufin O-deethylase (EROD) activity in seven fetal liver samples (unreported gestational age) that was inhibited to a variable extent by an anti-rat CYP1A1 monoclonal antibody. Similarly, Yang et al (1995) demonstrated EROD activity (6.2 pmol/min/mg of microsomal protein) in 8 to 10 pooled embryonic liver samples at 7 to 9 weeks estimated gestational age.…”
Section: Ontogeny Of the Cytochromes P450mentioning
confidence: 99%